2014
DOI: 10.2174/1381612820666140826113731
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Inhibitors as Therapeutics for Traumatic Brain Injury

Abstract: Developing therapeutics for traumatic brain injury remains a challenge for all stages of recovery. The pathological features of traumatic brain injury are diverse, and it remains an obstacle to be able to target the wide range of pathologies that vary between traumatic brain injured patients and that evolve during recovery. One promising therapeutic avenue is to target the second messengers cAMP and cGMP with phosphodiesterase inhibitors due to their broad effects within the nervous system. Phosphodiesterase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 168 publications
1
13
0
1
Order By: Relevance
“…Therefore, these results might be of relevance in clinical practice to optimize the conditions for promoting and preserving the quality of oocytes during handling and culture of COCs retrieved from patients enrolled in programs of assisted reproduction. In addition, it will be of interest to determine whether the dual action of cAMP in the cumulus is exerted also on other HA-rich tissues, particularly at the inflammation site, where hyaluronan is expressed (92) and the protective effect of cAMP elevation through phosphodiesterase inhibitors has been proven (93)(94)(95).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results might be of relevance in clinical practice to optimize the conditions for promoting and preserving the quality of oocytes during handling and culture of COCs retrieved from patients enrolled in programs of assisted reproduction. In addition, it will be of interest to determine whether the dual action of cAMP in the cumulus is exerted also on other HA-rich tissues, particularly at the inflammation site, where hyaluronan is expressed (92) and the protective effect of cAMP elevation through phosphodiesterase inhibitors has been proven (93)(94)(95).…”
Section: Discussionmentioning
confidence: 99%
“…Those results suggested that modulation of the cAMP pathway could have therapeutic potential in preventing memory deficits following primary bTBI. Intriguingly, increasing cAMP through phosphodiesterase-4 inhibition was effective in improving outcome in some experimental models of TBI and also reduced cognitive impairments associated with Alzhemer’s disease, schizophrenia and aging (Gong et al, 2004; Maxwell et al, 2004; Smith et al, 2009; Titus et al, 2014; Wiescholleck and Manahan-Vaughan, 2012). Currently, there are no clinically-approved treatments for TBI (Silverberg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PDEs as PDE4 and PDE7 are mainly selective on hydrolysis of cAMP whereas, PDE5, PDE6 and PDE9 are selective on cGMP. Since cGMP accumulation inhibits inflammation, the selective PDE5 inhibitors as sildenafil, tadalafil and vardenafil may seem good candidates for targeting UC diseases in which inflammation plays a central role (Keravis and Lugnier, 2012;Titus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%